Upaya Pelestarian Sulaman Kombinasi Berbasis Sulam Bayang Di Rumah Sulaman Cici Koto Gadang - Nabila Delfani; Ade Putra (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
Sulam bayang is a traditional embroidery technique native to West Sumatra, possessing high aesthetic and philosophical values. However, its existence is increasingly threatened as it is now preserved only by a handful of artisans. One of the few places that consistently maintains this technique is Rumah Sulaman Cici in Koto Gadang, which has even developed it into combination embroidery through various product innovations. This study aims to describe the preservation efforts of combination embroidery based on sulam bayang conducted at Rumah Sulaman Cici, as well as to analyze the balance between product innovation and the maintenance of traditional values within the embroidery practice. This research employs a qualitative method with a descriptive approach. Data were collected through direct observation, in-depth interviews with the business owner, artisans, and sales partners, as well as documentation. The findings reveal that Rumah Sulaman Cici implements three main preservation strategies, namely: (1) maintaining sulam bayang as the core technique in every combination embroidery piece; (2) preserving traditional Koto Gadang floral motifs as a consistent visual identity; and (3) conducting sulam bayang training activities as a means of transferring skills to the next generation. This study concludes that the preservation approach at Rumah Sulaman Cici is integrative, combining sustainable production practices, adaptive innovation, and skill inheritance into a cohesive and mutually reinforcing strategy